2021
DOI: 10.1155/2021/2672516
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Shexiang Baoxin Pill for Coronary Heart Disease after Percutaneous Coronary Intervention: A Systematic Review and Meta-analysis

Abstract: Objective. Shexiang Baoxin Pill (SBP) is a licensed Chinese herbal pharmaceutical that has been widely accustomed to treat coronary heart disease (CHD) after percutaneous coronary intervention (PCI). This study points to systematically assess the efficacy and security of the combination of SBP with conventional western medicine in the treatment of CHD after PCI. Methods. Databases including PubMed, the Cochrane Library, Web of Science, Embase, CNKI, Wanfang, VIP, and SINOMED were searched to collect RCTs on SB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The underlying rationale for this phenomenon could be ascribed to the suboptimal sensitivity of TTC staining in infarction size detecting ( Ito et al, 1997 ). Some clinical studies ( Qin et al, 2021 ; Wei et al, 2021 ) have found that SBP increased LVEF and decreases BNP levels. However, our study results were not entirely consistent with this finding.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying rationale for this phenomenon could be ascribed to the suboptimal sensitivity of TTC staining in infarction size detecting ( Ito et al, 1997 ). Some clinical studies ( Qin et al, 2021 ; Wei et al, 2021 ) have found that SBP increased LVEF and decreases BNP levels. However, our study results were not entirely consistent with this finding.…”
Section: Discussionmentioning
confidence: 99%
“…Prior evidence indicates that SBP has a therapeutic effect on all types of chronic coronary syndromes (CCS) and acute coronary syndromes (ACS) [22], and long-term application can improve the symptoms of patients with coronary heart disease and reduce cardiovascular events [14,28]. The findings were reported by a systematic review and meta-analysis of 19 eligible trials concluding that the combination of SBP with conventional treatment trial groups could significantly reduce the incidence of MACE, enhance left ventricular ejection fraction (LVEF), and lessen N-terminal pro-B-type natriuretic peptide (NT-pro-BNP) levels [29]. Similarly, the results from a systematic review and network meta-analysis of 179 eligible trials suggested that SBP combined with Western medicine is presumably the optimal treatment prescription for both clinically effective and cardiovascular event rates [30].…”
Section: Introductionmentioning
confidence: 99%
“…CVD was still one of the leading causes of morbidity and mortality worldwide, accounting for approximately 31.5% of deaths worldwide and 45% of deaths from noncommunicable diseases (16)(17)(18). CVD shared many risk factors with MAFLD, including diabetes, abnormal lipid metabolism, hypertension, insulin resistance, and inflammation (9,19).…”
Section: Introductionmentioning
confidence: 99%